Optimizing Employee Performance: The Role of Training, Discipline, and Career Development - Sihaloho, Riston; Farida Ferine, Kiki; Rahayu, Sri (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
This study aims to analyze the influence of training, work discipline, and career development on employee performance, as well as to examine the moderating effects of interactions among these variables on performance. The research employs a quantitative approach using Partial Least Squares (PLS) analysis. Data was collected through questionnaires distributed to 65 respondents. The results show that training, work discipline, and career development have a positive and significant effect on employee performance. This indicates that better training, higher discipline, and clearer career development lead to improved employee performance. However, the first and second moderating effects were found to be not significant, suggesting that the interactions among variables do not strengthen the relationship with performance. These findings imply that organizations should focus more on enhancing the main variables to improve employee performance.